An admittance-controlled wheeled mobile manipulator for mobility assistance: Human–robot interaction estimation and redundancy resolution for enhanced force exertion ability. (April 2021) - Xing, Hongjun; Torabi, Ali; Ding, Liang; Gao, Haibo; Deng, Zongquan; Mushahwar, Vivian K.; Tavakoli, Mahdi
Abstract: In this paper, a novel robotic assistive system (RAS) for mobility assistance of elderly adults is developed based on admittance control with force exertion ability enhancement (FEAE) of a wheeled mobile manipulator (WMM). The RAS can provide supportive force in the vertical direction and be guided by the user with a limited horizontal plane ability. An admittance controller is adopted to realize compliant behaviour between the end-effector and the user, enabling different admittance performances in different directions without requiring the complex system dynamics. The end-effector force needed by the controller is estimated by employing a nonlinear disturbance observer, avoiding the need for pricey force/torque (F/T) sensor. Meanwhile, with consideration of the limited joint torque output, the FEAE approach is implemented in the null-space of the WMM, which can make the system exert more Cartesian force in a given direction with consideration of Cartesian stiffness requirement using the same joint torque limitation through kinematic reconfiguration. Thus, it improves the capability of the system in realizing the desired admittance requirement. The advantages and effectiveness of the proposed approach are experimentally demonstrated with a 4-wheel omnidirectional mobile manipulator.